Gender, Labour, War and Empire - Levine, Philippa. author. aut Link
XIII, 282 p.
Keywords: A lively collection of essays on the cultures of nineteenth and twentieth-century Britain. Topics range from prostitution and slavery to the effect of war on fashion magazine reporting to inter-racial marriage in the postwar years. Particular areas of focus include the Second World War, its legacies and the reactions to postwar decolonization.